Perception that Mothers and / or Guardians of Overweight or Obese Preschool Children Have of a Text Messaging Program to Support Behaviour Change in their Children - Solange Parra-Soto MSc; Alejandra Ortega MSc; Carlos Celis-Morales PhD; Juliana Kain MSc (SAGE Publishing, 2020)
In most childhood obesity preventive programs, parents are targeted as they are key in achieving lifestyle behavior change in their children. Because their participation is generally low, new technologies, such as text messaging, are being tested to assess if their participation increases. The objective of this study was to determine the perception that mothers of overweight/ obese preschool children have of a textmessaging program developed to support their children's lifestyle behavior change. Text messages were sent to 60 mothers twice a week for 12 weeks; 58 of them said they received all of them. During the process mothers were contacted twice regarding their opinion on all aspects related to the messages. At follow-up, we determined perception by in depth interviews administered to participants. Results show that text messaging implemented in a personalized manner was considered successful in regards to providing useful information to support their children's behavior change.